P‐113: Speckle Suppression in a MEMS Scanning Blue‐LD/Phosphor White Light by using Overlapping Diversity for Lighting Source Application. Issue 1 (May 2016) - Tu, Shih-Yu; Lin, Hoang Yan; Lee, Tsung-Xian
Abstract : We have demonstrated efficient speckle reduction techniques by using both overlapping and mixing techniques. A phosphor sample is used for white light generation. The speckle contrast (SC) can be reduced from 38.5% to 7.8% for a MEMS scanning blue LD area. The speckle‐free results are achieved for mixed white light source.